Novel anti-inflammatory activity of epoxyazadiradione against macrophage migration inhibitory factor inhibition of tautomerase and proinflammatory activities of macrophage migration inhibitory factor - Alam, Athar; Haldar, Saikat; Thulasiram, Hirekodathakallu V.; Kumar, Rahul; Goyal, Manish; Iqbal, Mohd Shameel; Pal, Chinmay; Dey, Sumanta; Bindu, Samik; Sarkar, Souvik; Pal, Uttam; Maiti, Nakul C.; et al. (Journal of Biological Chemistry, 2012)
Macrophage migration inhibitory factor (MIF) is responsible for proinflammatory reactions in various infectious and noninfectious diseases. We have investigated the mechanism of anti-inflammatory activity of epoxyazadiradione, a limonoid purified from neem (Azadirachta indica) fruits, against MIF. Epoxyazadiradione inhibited the tautomerase activity of MIF of both human (huMIF) and malaria parasites (Plasmodium falciparum (PfMIF) and Plasmodium yoelii (PyMIF)) non-competitively in a reversible fashion (K-i, 2.11-5.23 mu M). Epoxyazadiradione also significantly inhibited MIF (huMIF, PyMIF, and PfMIF)-mediated proinflammatory activities in RAW 264.7 cells. It prevented MIF-induced macrophage chemotactic migration, NF-kappa B translocation to the nucleus, up-regulation of inducible nitric-oxide synthase, and nitric oxide production in RAW 264.7 cells. Epoxyazadiradione not only exhibited anti-inflammatory activity in vitro but also in vivo. We tested the anti-inflammatory activity of epoxyazadiradione in vivo after co-administering LPS and MIF in mice to mimic the disease state of sepsis or bacterial infection. Epoxyazadiradione prevented the release of proinflammatory cytokines such as IL-1 alpha, IL-1 beta, IL-6, and TNF-alpha when LPS and PyMIF were co-administered to BALB/c mice. The molecular basis of interaction of epoxyazadiradione with MIFs was explored with the help of computational chemistry tools and a biological knowledge base. Docking simulation indicated that the binding was highly specific and allosteric in nature. The well known MIF inhibitor (S, R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1) inhibited huMIF but not MIF of parasitic origin. In contrast, epoxyazadiradione inhibited both huMIF and plasmodial MIF, thus bearing an immense therapeutic potential against proinflammatory reactions induced by MIF of both malaria parasites and human.